2021
DOI: 10.1016/j.jcmgh.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal α1-2-Fucosylation Contributes to Obesity and Steatohepatitis in Mice

Abstract: Intestinala1-2-fucosylation mediates host-microbe interactions and can shape the metabolism of intestinal microorganisms. Here, we identified that mice lacking a1-2fucosylation were protected from Western diet-induced features of obesity and steatohepatitis and this protection was mediated through the intestinal microbiota.BACKGROUND & AIMS: Fucosyltransferase 2 (Fut2)-mediated intestinal a1-2-fucosylation is important for host-microbe interactions and has been associated with several diseases, but its role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The macronutrient composition of the diet, the duration of feeding, and the genetic background of the animals are all important variables in determining disease severity in preclinical MAFLD models 44 . To establish an ideal MAFLD model, several attempts have been made to use HFD in combination with fructose and sucrose-enriched drinking water 45,46 . In this study, we have constructed the MAFLD model using the mouse strain derived from the C57BL/6 J and 129S6/SvEvTac, which may serve as a suboptimal model to investigate advanced stages of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The macronutrient composition of the diet, the duration of feeding, and the genetic background of the animals are all important variables in determining disease severity in preclinical MAFLD models 44 . To establish an ideal MAFLD model, several attempts have been made to use HFD in combination with fructose and sucrose-enriched drinking water 45,46 . In this study, we have constructed the MAFLD model using the mouse strain derived from the C57BL/6 J and 129S6/SvEvTac, which may serve as a suboptimal model to investigate advanced stages of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, one study reported that Fut2-deficient mice were protected from western diet–induced obesity and steatohepatitis, and another showed that Fut2 mutation leads to liver disease. 64 , 65 Interestingly, in our study, we found a significant increase in Fut2 expression in the jejunum, ileum and colon, only in the group supplemented with FOS, suggesting that it could indeed be associated with the protection against diet-induced obesity.…”
Section: Discussionmentioning
confidence: 44%
“…Metagenomics has become a well-established approach for profiling microbial communities and studying microbiomes in the environment, as well as in health and disease ( 1 ). Correlating shifts in the relative composition of microbial communities among different conditions to draw explanatory hypotheses is the goal of many microbiome surveys ( 2 4 ). A fundamental setback limitation of these studies is that taxon abundances are calculated consisting of only relative values ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%